What lies beneath: an eco-historical view of high andes water pollution - Williams,Heather (2015)
This article in two parts provides a sketch of the Suma Quta (in Aymara language, "Beautiful Lake") Project, an experiment in "bottom-up science" begun in the Lake Titicaca basin in Peru in 2009. The article explores the question of why water resource and fisheries management has fallen into crisis in what has been in millennial terms one of the world's most meticulously managed hydroscapes. It argues that post-Conquest patterns of village autonomy and militant self-management of natural resources have rendered rural villages highly vulnerable to pollution from extractive industries and subsequent informal urbanization. Civil society initiatives on water quality are therefore most likely to succeed where they enable communities to collect watershed data and take action independently while maintaining contact with other communities in a horizontal, leaderless network.